3ax-b=d-4cxplease note every step
3ax - b = d - 4cx
I am assuming that you need to rewrite the equation with x on a side by itself:
First let us group the terms containing x , on the left sides:
3ax + 4cx = d + b
Now factor x:
x (3a + 4c) = d+b
Now divide by (3a + 4c)
==> x = (d+b)/(3a+4c)
Given a, b, c, and d, you could calculate x value.
Based on the fact that the given expression contains the variable x, we'll determine x.
Fot this rason, we'll move all terms to one side. We'll start by subtracting d both sides:
3ax-b-d = +d-d-4cx
We'll eliminate like terms:
3ax-b-d = -4cx
Now, we'll add 4cx both sides:
3ax-b-d + 4cx = -4cx + 4cx
3ax-b-d + 4cx = 0
We'll combine like terms, namely the terms that contain x and the terms without x:
(3ax+ 4cx) + (-b-d) = 0
We'll factorize by x:
x(3a+4c) + (-b-d) = 0
We'll subtract (-b-d) both sides:
x(3a+4c) = -(-b-d)
x(3a+4c) = b+d
We'll divide by (3a+4c), to isolate x:
x = ( b+d) / (3a+4c)
To solve for x.
This is a simple equation containing the variable x. We solve for x.
We collect x's together by adding 4cx to both sides.
3ax-b+4cx = d-4cx+4cx. -4cx+4cx becomes zero.
3ax+4cx -b = d. Add b to both sides:
3ax+4cx -b+b = d+b. -b+b becomes zero on the left.
3ax+4cx = d+b
(3a+4c)x = b+d. 3ax+4cx = (3a+4c)x distributive property of multiplication. d+b =b+d by commutative property of addition.
Divide both sides by 3a+4c.
(3a+4c)x/(3a+4c) = (b+d)/(3a+4c)
x = (b+d)/(3a+4c).